Characterisation of antimony, arsenic, cadmium, copper and tin occurrences at an abandoned sulphide-mining area. (30th June 2010) - Landsberger, Sheldon; Robinson, Sam; Freitas, Maria Do Carmo; Canha, Nuno; Pacheco, Adriano; Anawar, Hossain
Contamination levels in top-soil, vascular plant and surface water samples from the Sao Domingos mining area, Portugal, were determined by Instrumental Neutron Activation Analysis (INAA) and Compton-Suppression Neutron Activation Analysis (CSNAA). The total levels of As, Cd, Cu, Sb and Sn are reported with a discussion of plant uptake and transfer coefficients. Comparative analysis of the same elements by the two methods has confirmed sample heterogeneity, and that CSNAA is adequate for the precise determination of As, Sb and other metals (Cd, Cu, Sn). Excessively high concentrations of As, Cu and Cd were found in 50% of the surface water samples, even above the toxicity threshold. The mining soil samples have extremely high concentrations of As, Sb and Cu. Despite the low concentrations of As, Sb, Cu and Sn in leaves, stems and roots, Erica andevalensis, Juncus acutus and Agrostis castellana might be suitable species for phytostabilisation.